Extended input-output model for urbanization: An empirical test using Chinese data - Nobuhiro Okamoto (Journal of Economic Structures, 2021)
Although the input-output model has been widely used for both pure economic analysis and environmental issues, demographic analysis has been relegated to the periphery of the input-output literature. Previous researchers have made significant contributions in developing the economic-demographic modeling from the unemployment perspective, in the context of shrinking regional economies. This study aims to develop an extended input-output model for urbanization, based on the Batey-Madden model by incorporating the "urbanization process". This process is associated with one of the facets of demographic change and has received little attention in the literature. The effectiveness of the model is theoretically explored and empirically tested using Chinese data, which show rapid progress of urbanization in China. The study proposes a new "urbanization multiplier", which implies intense population concentration in cities based on an employment multiplier in urban areas and labor allocation possibilities between urban and rural areas. The result from a preliminary application shows that the economic structure can determine the urbanization multiplier, indicating that the extent of employment opportunities promotes urbanization and the size of the population attracts more workers from rural areas. The model provides a fresh aspect of urbanization in the existing literature.
Keywords: 330; Demography; Input-output analysis; Migration; Urbanization